2009
DOI: 10.1038/ismej.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Towards the definition of a core of microorganisms involved in anaerobic digestion of sludge

Abstract: The microbial consortium involved in anaerobic digestion has not yet been precisely characterized and this process remains a 'black box' with limited efficiency. In this study, seven anaerobic sludge digesters were selected based on technology, type of sludge, process and water quality. The prokaryotic community of these digesters was examined by constructing and analysing a total of 9890 16S rRNA gene clones. Libraries were constructed using primers specific for the Bacteria and Archaea domains for each diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
423
3
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(481 citation statements)
references
References 40 publications
35
423
3
9
Order By: Relevance
“…This study also constructed much more complete genomes of Pseudothermotoga, Mesotoga, Caldiserica 31q06 and Cloacimonetes. Moreover, this effort generated genomes for taxa that our previous study could not address, including uncultivated phyla Atribacteria, Hydrogenedentes, Marinimicrobia and WS1; poorly understood phyla Armatimonadetes and Chloroflexi; and other uncultivated phylogenetic branches of novel Caldisericia sister clade, Syntrophus-related clade, Spirochaetes SA-8, Synergistetes TTA-B6, Planctomycetales-related clade and Phycisphaerae-related cluster WPS-1 (Chouari et al, 2005;Riviere et al, 2009;Yamada and Sekiguchi, 2009 Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also constructed much more complete genomes of Pseudothermotoga, Mesotoga, Caldiserica 31q06 and Cloacimonetes. Moreover, this effort generated genomes for taxa that our previous study could not address, including uncultivated phyla Atribacteria, Hydrogenedentes, Marinimicrobia and WS1; poorly understood phyla Armatimonadetes and Chloroflexi; and other uncultivated phylogenetic branches of novel Caldisericia sister clade, Syntrophus-related clade, Spirochaetes SA-8, Synergistetes TTA-B6, Planctomycetales-related clade and Phycisphaerae-related cluster WPS-1 (Chouari et al, 2005;Riviere et al, 2009;Yamada and Sekiguchi, 2009 Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenedentes' (formerly NKB19): a lipolytic glycerol degrader Hydrogenedentes is often associated with methanogenic environments (Riviere et al, 2009;Narihiro et al, 2014), but its ecological role has remained enigmatic. While the genomic technology available for our previous study was insufficient for metagenomically capturing Hydrogenedentes, implementing modern sequencing platforms allowed construction of a Hydrogenedentes pangenome and transcriptome.…”
Section: Metatranscriptomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher relative abundance of γ-Proteobacteria, Firmicutes and Chloroflexi and a lower proportion of β-Proteobacteria and ε-Proteobacteria sequences was detected at the downstream site compared to the upstream site. The higher proportion of Firmicutes and Chloroflexi sequences reflects the impact of RWTP effluent, because some members of these phyla have been proposed as indicators of fecal pollution, and they were commonly abundant in anaerobic wastewater treatment systems (Riviere et al, 2009). Previous studies have also demonstrated that the class Clostridia, which was dominant among the Firmicutes at the downstream point, has frequently been detected within urban wastewater systems (Vierheilig et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…DFM on microbial interactions was difficult to analyse (Figure 4). The main identified microbial groups, for example Bacteroidetes, Bacilli, Clostridia encompass most of known fermentative bacteria in pig manure (Peu et al, 2006) as well as in anaerobic digesters (Liu et al, 2009;Riviere et al, 2009). …”
Section: Discussionmentioning
confidence: 99%